First Record of Diarrhetic Shellfish Poisoning (DSP) Toxins in Perna Perna (Linnaeu, 1758) Mussels from a Mariculture Farm at the Marine Extractive Reserve in Arraial Do Cabo, RJ, Southeastern Brazil in the Summer of 2014 - Daniela Almeida de Souza; Maria Helena Campos Baeta Neves; Mathias Alberto Schramm; Luis Antônio de Oliveira Proença; Rachel Ann Hauser-Davis; Renato Matos Lopes; Victor Barbosa Saraiva; Manildo Marcião de Oliveira (Thalassas: An International Journal of Marine Sciences, 2025)

Prolonged Siberian heat of 2020 almost impossible without human influence - Andrew Ciavarella; Daniel Cotterill; Peter Stott; Sarah Kew; Sjoukje Philip; Geert Jan van Oldenborgh; Amalie Skålevåg; Philip Lorenz; Yoann Robin; Friederike Otto; Mathias Hauser; Sonia I. Seneviratne; et al. (Climatic Change, 2021)
Over the first half of 2020, Siberia experienced the warmest period from January to June since records began and on the 20th of June the weather station at Verkhoyansk reported 38 °C, the highest daily maximum temperature recorded north of the Arctic Circle. We present a multi-model, multi-method analysis on how anthropogenic climate change affected the probability of these events occurring using both observational datasets and a large collection of climate models, including state-of-the-art higher-resolution simulations designed for attribution and many from the latest generation of coupled ocean-atmosphere models, CMIP6. Conscious that the impacts of heatwaves can span large differences in spatial and temporal scales, we focus on two measures of the extreme Siberian heat of 2020: January to June mean temperatures over a large Siberian region and maximum daily temperatures in the vicinity of the town of Verkhoyansk. We show that human-induced climate change has dramatically increased the probability of occurrence and magnitude of extremes in both of these (with lower confidence for the probability for Verkhoyansk) and that without human influence the temperatures widely experienced in Siberia in the first half of 2020 would have been practically impossible.

Evaluation of the HadGEM3-A simulations in view of detection and attribution of human influence on extreme events in Europe - Robert Vautard; Nikolaos Christidis; Andrew Ciavarella; Carmen Alvarez-Castro; Omar Bellprat; Bo Christiansen; Ioana Colfescu; Tim Cowan; Francisco Doblas-Reyes; Jonathan Eden; Mathias Hauser; Gabriele Hegerl; et al. (Climate Dynamics, 2019)

Multiple perspectives on the attribution of the extreme European summer of 2012 to climate change - Laura J. Wilcox; Pascal Yiou; Mathias Hauser; Fraser C. Lott; Geert Jan van Oldenborgh; Ioana Colfescu; Buwen Dong; Gabi Hegerl; Len Shaffrey; Rowan Sutton (Climate Dynamics, 2018)

Erratum to: Western US high June 2015 temperatures and their relation to global warming and soil moisture - Sjoukje Y. Philip; Sarah F. Kew; Mathias Hauser; Benoit P. Guillod; Adriaan J. Teuling; Kirien Whan; Peter Uhe; Geert Jan van Oldenborgh (Climate Dynamics, 2018)

Western US high June 2015 temperatures and their relation to global warming and soil moisture - Sjoukje Y. Philip; Sarah F. Kew; Mathias Hauser; Benoit P. Guillod; Adriaan J. Teuling; Kirien Whan; Peter Uhe; Geert Jan van Oldenborgh (Climate Dynamics, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)